Lignin Depolymerization: A Comparison of Methods to Analyze Monomers and Oligomers. Issue 17 (13th July 2020) - Bartolomei, Erika; Le Brech, Yann; Dufour, Anthony; Carre, Vincent; Aubriet, Frederic; Terrell, Evan; Garcia‐Perez, Manuel; Arnoux, Philippe
Abstract: Catalytic liquefaction of lignin is an attractive process to produce fuels and chemicals, but it forms a wide range of liquid products from monomers to oligomers. Oligomers represent an important fraction of the products and their analysis is complex. Therefore, rapid characterization methods are needed to screen liquefaction conditions based on the distribution in monomers and oligomers. For this purpose, UV spectroscopy is proposed as a fast and simple method to assess the composition of lignin‐derived liquids. UV absorption and fluorescence were studied on various model compounds and liquefaction products. Liquefaction of Soda lignin was conducted in an autoclave, in ethanol and with Pt/C catalyst (H2, 250 °C, 110 bar). Liquids were sampled at isothermal conditions every 30 min for 4 h. UV fluorescence spectroscopy is related to GC–MS, gel‐permeation chromatography (GPC), MALDI‐TOF MS, and NMR characterizations. A depolymerization index is proposed from UV spectroscopy to rapidly assess the relative distribution of monomers and oligomers. Abstract : Lignin analysis how‐to : The methods used to analyze monomers and oligomers produced from catalytic lignin liquefaction are evaluated and their pitfalls and benefits discussed. UV fluorescence is highlighted as a simple and fast method to analyze the relative distribution between monomers, oligomers and heavier fractions.